Sexuality and the Dimensions of Power - Brickell, Chris (Sexuality & Culture : An Interdisciplinary Quarterly, 2009)
Power, many scholars agree, is intrinsic to the relationships between sexuality, individual experience and social dynamics. Beyond this basic agreement, though, writers and researchers have adopted different foci. This article critically reviews several approaches to the power-sex relationship, and suggests that four readily discernable but interlaced dimensions of power operate upon the sexual: definitional, regulatory, productive and unequal. As a number of examples from the literature show, these ideal typical forms twist and interweave in both theory and practice. I suggest that to be mindful of all four facets of power and their interrelationships is to account for multiplicity, and to avoid the reductive characterizations that have sometimes characterized academic writings on power and sexuality. In this way, both theory and research in the area of human sexuality can be more thoroughly conceptualized.
Keywords: approches et analyses; cours; discipline; hétérosexisme; premier cycle; queer; rapports de pouvoir; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

Whose `Special Treatment'? Heterosexism and the Problems with Liberalism - Brickell, Chris (Sexualities, 2001)
This article examines the circulation of heterosexist positions within several recent New Zealand media texts. It argues that a recent form of discourse engages liberal language and assumptions in ways that support the privileged position of heterosexuality and the marginalization of homosexuality. The examples given highlight not only the tenor of some recent representations of homosexuality, but also some problems within liberalism. Most notable of these are liberalism's individualism and its failure to recognize the systemic nature of hierarchical power relationships and the constituting of lesbian and gay subjectivities within these relationships. These problems allow liberalism to play an active part in processes of domination and subordination.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; discours médiatique; histoire; hétérosexisme; libéralisme; nouvelle-zélande; océanie; premier cycle; périodes historiques; rapports de domination; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences